Strengthening Character Education Based on Local Wisdom "Local Wisdom" (Study in Leuweung Kolot) - Milahtul Latifah (al-Afkar, Journal For Islamic Studies, 2024)
Character education is actually as old as the history of education itself. Ethno pedagogy (local wisdom)-based education is an educational practice where knowledge is generated, stored, applied, and passed down through local wisdom in an area. Furthermore, local wisdom means; an outlook on life, knowledge, and various life strategies in the form of activities, carried out by local communities to answer various problems in meeting their needs. The lecture method is used to explain material that has been prepared by the implementing team. The Question and Answer method is used to facilitate workshop participants in responding to and understanding the material presented by the implementing team. Discussion Method, namely the implementing team conducts dialogue with Workshop participants regarding things that need to be considered for strengthening in the form of character education through local wisdom in Leuweung Kolot village. Seren Taun is a tradition of Sundanese karuhun residents of Leuweung Kolot, Cibungbulang District, Abah Lihin Sabondoroyot Kp. Bubulak RT. 05 rw. 01, dressed up for a big celebration and at Kp. Cipakel RT. 05 RW. 05 held a ritual of thanksgiving for the harvest. The aura of the celebration began to be felt as soon as you entered the courtyard. It starts to get busy with residents and guests from various regions the day before the peak of the annual event. "Seren itself means handing over or handing over, year means year. People interpret Seren Taun as a ceremony for handing over alms (totali) from the rice harvest for a year and asking for blessings from God so that the next year's harvest will increase. The character education that is being developed is handing over everything to Allah (Tawakal) Seren Tahun (1 year) so that it becomes a blessing, and then expressions of gratitude with joy are celebrated with various events at KP. Bubulak.